ROLE OF ACTIVATED INTRARENAL REACTIVE OXYGEN SPECIES AND RENIN–ANGIOTENSIN SYSTEM IN IgA NEPHROPATHY MODEL MICE - Ohashi, Naro (2009)
1. Using HIGA (high IgA of ddY) mice as an IgA nephropathy model and BALB/c mice as controls, we demonstrated that reactive oxygen species (ROS) and the renin–angiotensin system (RAS) were activated in kidneys of HIGA mice. However, it was difficult to establish an association between renal damage and changes in ROS and the RAS. Therefore, the present study was performed to determine whether renal injury is associated with changes in ROS and the RAS in HIGA mice. 2. Male HIGA mice were divided into four groups of 10 each: (i) untreated mice (HIGA + null); (ii) mice treated with the angiotensin AT(1) receptor antagonist olmesartan (5 mg/kg per day; HIGA + OLM); (iii) mice treated with the superoxide dismutase mimetic tempol (50 mg/kg per day; HIGA + Tempol); and (iv) mice treated with RAS-independent antihypertensive drugs (30 mg/kg per day hydralazine, 0.6 mg/kg per day reserpine and 12 mg/kg per day hydrochlorothiazide; HIGA + HRH). Mice were treated for 5 weeks. 3. Systolic blood pressure decreased significantly in the HIGA + OLM and HIGA + HRH groups, but not in the HIGA + Tempol group, compared with HIGA + null mice. The expression of two ROS markers (4-hydroxy-2-nonenal and heme oxygenase-1) and angiotensin II as a marker of the RAS decreased significantly in HIGA + OLM and HIGA + Tempol mice, but not in HIGA + HRH mice, compared with HIGA + null mice. As a marker of renal damage, mesangial matrix expansion and the desmin-positive area decreased significantly in the HIGA + OLM and HIGA + Tempol groups, but not in HIGA + HRH group, compared with the HIGA + null group. 4. These data suggest that intrarenal ROS and RAS activation play a pivotal role in the development of IgA nephropathy model mice, from the early phase, independent of blood pressure.